Comparation between two methods of harvesting and hauling of banana in Costa Rica - Díaz Gutiérrez, Carlos (2023)
The objective of the study was to carry out a technical and financial comparative analysis generated by the method of harvesting and hauling of banana to the production plant, according to the conventional system or “pulled by human traction” against the method of “harvesting and hauling with animal traction”, in order for the Company to have a decision- making tool which minimizes the cost of internal transportation by having more efficient ways of transporting fruit from the plantation to the packing area; this reflects a positive impact on the search for improvements in financial profitability, which is the basis for the maintenance and growth of companies. The research, which was developed in 2021, was proposed as a study case in a farm located in the North Caribbean of Costa Rica, with a dimension of 700 hectares of fruit; for the technical evaluation, a flowchart was used, which identifies the required activities for the harvesting and hauling, and then in work sessions carried out with the farm administrators, the structures of items and monetary amounts of the activities of harvesting and transporting the fruit were identified, known as the structures of costs and investments for both the current system or human traction and for the proposal of harvest and transport with the use of animal traction. The processing of the primary monetary data was carried out with the help of Excel sheets based on the budget of the farm during year 2021. The best results of harvesting and transporting the fruit were achieved when the “harvesting and hauling with animal traction” method is used, reducing the harvesting, and transporting time by 0.54 minutes decreasing by U.S. $0.02 when using the mule system, this is produced mainly by the savings generated in labor between both systems. When applying the indicator of the Present Value of Costs (PVC), it was shown how the farm generates savings in present value of costs of U.S. $ 34 384,04.